Evaluation of recessed and bar handles of freezer door in refrigerator - Jung, Myung Chul; Hwang, Jaejin (Human Factors and Ergonomics In Manufacturing, 2020)
Design components of handles can affect the physical demands on users and their satisfaction. However, few studies have evaluated the physical usability of different handle configurations in refrigerators. The objective of this study was to evaluate the effect of the handle height, clearance, embossing, and users’ stature on their physical demands and satisfaction with two different handle types. Twenty-eight participants were recruited, and several design components, including the handle type (recessed, bar), height (620 and 680 mm), clearance (0, 3, 5, and 7 mm), embossing (with and without), and users’ stature (short, medium, and tall) were investigated. Regardless of handle type, higher handle (680 mm) exhibited a lower flexion angle and flexion moments of the hips and back compared with lower handle (620 mm), and participants expressed greater satisfaction with embossed handles when using the recessed handle. Handle height and comfortable grip configuration were the primary components that affected physical usability. The results could be useful in designing and improving refrigerator handles.
Keywords: Design Component; Flexion moments; Physical demand; biomechanics; freezer; handle height; handle type; satisfaction